2019
DOI: 10.1039/c9ra04761a
|View full text |Cite
|
Sign up to set email alerts
|

Formation of concentrated triglyceride nanoemulsions and nanogels: natural emulsifiers and high power ultrasound

Abstract: The capability of ultrasonication and natural emulsifiers on nano-emulsification and nano-gelation of concentrated triglyceride oil was verified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…5−8 However, most of used nanoemulsions have liquid-like behavior at ambient temperature, which limits their application in cosmetic, food, and pharmaceutical products. 9,10 The application of nanoemulsions depends on their structures, such as oil volume fraction, droplet size, and surface charge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5−8 However, most of used nanoemulsions have liquid-like behavior at ambient temperature, which limits their application in cosmetic, food, and pharmaceutical products. 9,10 The application of nanoemulsions depends on their structures, such as oil volume fraction, droplet size, and surface charge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Titration blank for the digesta was performed in the absence of enzymes, and the volume of NaOH used was deducted from the respective titration volume of each sample. The digestion curves were obtained for three replicates with a data acquisition frequency of 2 per s. From the data, the percentage of FFA released was calculated using eqn (3).…”
Section: Food and Function Papermentioning
confidence: 99%
“…In particular, concentrated food emulsions in creams, sauces, salad dressings, mayonnaises, and spreads are of significant importance in which the emulsion droplet size, oil volume fraction, interfacial composition, and inter-droplet interactions control the overall structure-functionality of the final products. [1][2][3] Many researchers have shown that the conversion of conventional emulsions with repulsive inter-droplet interaction into nanoemulsions can significantly affect their rheology. 4,5 Considering the core-shell structure of droplets, according to eqn (1), repulsive gelation in concentrated nanoemulsions can be achieved at a significantly reduced oil volume fraction (ϕ oil ) compared to the conventional emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Shear sweeps were conducted at 25 ºC between 0.001 to 1000 s -1 so as to obtain flow curves. Flow behavior of the dispersions were assessed by fitting the shear rate versus shear stress values to five usual models, i.e., Newtonian (τ = ṁ), Power-law (τ = ṁn), Herschel-Bulkley (τ = ṁn + 0 ), Bingham (τ = ṁ + 0 ), and Casson (√ = m�̇ + � 0 ), Where τ is the shear stress (Pa), m is the consistency coefficient (Pa.sn), ̇ is the shear rate (1 s -1 ), the exponent n is flow behavior index (dimensionless) and τ0 is the yield stress (Pa) (Nejatian and Abbasi, 2019;Nejatian et al, 2018).…”
Section: Rheological Measurementsmentioning
confidence: 99%